Islam and Nigerian foreign policy (1960-2015) - Abubakar, Abubakar Usman; Abdel Salam, El Fatih Abdullahi (2016)
Some widely believed guesstimates have Nigerian Muslims constituting 50 percent of the country’s population. This number translates into 5 percent of the world total Muslim population and one-third of the total number of Muslims in the Sub-Saharan Africa region. With the increasing role Islam plays in international relations, this study aims to explore the role Islam, as one of the major religions in Nigeria, plays in its foreign policy by assessing processes, procedures and implementation of Nigerian foreign policy. Although Islam is arguably the biggest religion in Nigeria, the country is stipulated by its constitution as secular. This particular fact makes any attempt to study the role of religion in the Nigerian public spheres complicated in nature. Nonetheless, using a framework introduced by Adeed Dawisha in his edited book “Islam and Foreign Policy”, the study argues that Islam influences Nigerian foreign policy through processes, procedures and personalities on the one hand and policy implementation on the other. The study concludes that despite being one of the biggest religions in the country, Islam has featured rather scantly in the country’s 55 years of independence.